Bibliometric analysis of scientific articles published in Brazilian and international orthodontic journals over a 10-year period - Neudí Antonio Primo; Vivian Bertoglio Gazzola; Bruno Tochetto Primo; Maximiano Ferreira Tovo; Italo Medeiros Faraco Junior (Dental Press Editora, 2014)
Objective: This study aimed at describing the profiles of Brazilian and international studies published in orthodontic journals. Methods: The sample comprised 635 articles selected from two scientific journals, i.e., Dental Press Journal of Orthodontics and American Journal of Orthodontics and Dentofacial Orthopedics, which were analyzed at three different intervals over a 10-year period (1999 - 2004 - 2009). Articles were described in terms of knowledge domain, study design, and country of origin (or state of origin for Brazilian papers). Results: The most frequent study designs adopted in international studies were cohort (23.9%) and cross-sectional (21.7%) designs. Among Brazilian papers, cross-sectional studies (28.9%) and literature reviews (24.6%) showed greater frequency. The topics most often investigated were dental materials (17%) and treatment devices (12.4%) in international articles, with the latter topic being addressed by 16% of the Brazilian publications, followed by malocclusion, with 12.6%. In all cases, the most frequent countries of origin coincided with the countries of origin of each journal. Conclusions: The majority of the studies analyzed featured a low level of scientific evidence. Moreover, the findings showed that journals tend to publish studies produced in their own country of origin, and that there are marked discrepancies in the number of papers published by different Brazilian states.